An Overview of Difficulties in Controlling Intensified Process - Reza Barzin; Syamsul Rizal Abd Shukor; Abdul Latif Ahmad (Department of Chemical Engineering, Universitas Gadjah Mada, 2007)
Process intensification (PI) is currently one of the most significant trends in chemical engineering and process technology. PI is a strategy of making dramatic reductions in the size of unit operations within chemical plants, in order to achieve production objectives. PI technology is able to change dramatically the whole chemical engineering industry pathway to a faster, cleaner and safer industry. Nonetheless, PI technology will be handicapped if such system is not properly controlled. There are some foreseeable problems in order to control such processes for instance, dynamic interaction between components that make up a control loop, response time of the instrumentations, availability of proper sensor and etc. This paper offers an overview and discussion on identifying potential problems of controlling intensified systems.